2014
DOI: 10.1016/j.tube.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome response in guinea pigs infected with the high virulence strain Mycobacterium tuberculosis TT372

Abstract: SUMMARY In this study we conducted a microarray-based whole genomic analysis of gene expression in the lungs after exposure of guinea pigs to a low dose aerosol of the Atypical Beijing Western Cape TT372 strain of Mycobacterium tuberculosis, after harvesting lung tissues three weeks after infection at a time that effector immunity is starting to peak. The infection resulted in a very large up-regulation of multiple genes at this time, particularly in the context of a “chemokine storm” in the lungs. Overall gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Lungs were harvested from the four studies above on day-30 and subjected to whole genomic analysis, as previously described [ 31 ].> What was immediately noticeable was that the number of genes turned on or off by the NOT isolates was far higher than that of the HT isolates ( Table 2 ). Within these, multiple genes of interest showed increased expression ( Table 3 ) while others were clearly down-regulated ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lungs were harvested from the four studies above on day-30 and subjected to whole genomic analysis, as previously described [ 31 ].> What was immediately noticeable was that the number of genes turned on or off by the NOT isolates was far higher than that of the HT isolates ( Table 2 ). Within these, multiple genes of interest showed increased expression ( Table 3 ) while others were clearly down-regulated ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Important hub-central genes of the turquoise module were included ACAA1 ( Behera et al, 2022 ), ACAD10 ( Nalpas et al, 2015 ), ACSS2 ( Koo et al, 2012 ), ALDH2 ( Park et al, 2014 ), ALDH9A1 ( Aiyaz et al, 2014 ), C1QA , C1QB , CIQC ( Cai et al, 2014 ), C3AR1 ( Zhang et al, 2019 ), ECHS1 ( Bell et al, 2017 ), EHHADH ( Aiyaz et al, 2014 ), FCGRA1 ( Jenum et al, 2016 ), LAPTM5 ( Kang et al, 2011 ), PCCA , PCCB ( Katiyar et al, 2018 ), PEPD ( White et al, 2010 ), TREM2 ( Iizasa et al, 2021 ), VPS11 , VPS18 ( Chandra et al, 2015 ), and VPS33B ( Mascarello et al, 2010 ), which were involved in the host immune response and bAMs- M. bovis interactions. For instance, ACAA1 is one of the core component of fatty acid metabolic process which encodes a hallmark enzyme of fatty acid β-oxidation, and it has been reported that M. tuberculosis increases the rate of fatty acid β-oxidation for its survival by enhancing the expression of this gene ( Behera et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that GGT7 levels helped predict TB progression in pregnant women before they developed symptomatic disease. GGT7 is involved in glutathione metabolism, which is important in the TB immune response and has been associated with TB disease [ 11 ]. This gene has not been identified in several TB progression studies [ 3 , 12 ], suggesting that glutathione pathways may be more important in maternal TB pathogenesis.…”
Section: Discussionmentioning
confidence: 99%